Analisis Faktor Konvensional & Syariah yang Melandasi Penggunaan Akuntansi Digital di UMKM Kecamatan Perhentian Raja Kabupaten Kampar - Natasya Deri Liana; Gina Havieza Elmizan (Lembaga Yasin AlSys, 2026)
The use of digital accounting by micro, small, and medium enterprises (MSMEs) plays an important role in improving the efficiency and quality of financial management. However, studies integrating conventional factors based on the Technology Acceptance Model (TAM) with Sharia factors based on Maqashid Sharia in explaining the use of digital accounting by MSMEs remain limited. This study aimed to analyze the conventional and Sharia factors underlying the use of digital accounting by MSMEs in Perhentian Raja Subdistrict, Kampar Regency. The study employed a qualitative approach with a descriptive design and involved 13 MSME actors selected through purposive sampling, incidental sampling, and saturated sampling. Data were collected through in-depth interviews, observation, and documentation and were subsequently analyzed using thematic analysis. The results showed that most MSME actors still used manual financial recordkeeping, and only a small proportion had adopted digital accounting. The conventional factors underlying the use of digital accounting included perceived usefulness, perceived ease of use, facilitating conditions, and price value. In addition, Sharia factors, particularly the principle of hifzh al-maal in Maqashid Sharia, were also considered in the use of digital accounting, especially in relation to data security, transparency, and the protection of business assets. These findings extend the study of technology adoption by integrating the TAM and Maqashid Sharia perspectives within the context of MSME financial management. In practical terms, the results emphasize the importance of training, assistance, and the development of digital accounting applications that are easy to use, secure, and aligned with the needs of Sharia-based MSMEs by the government, MSME support institutions, and application developers.